INDONESIAN RELATIVE CLAUSES AND ITS SIMILARITIES IN FOREIGN LANGUAGE - Rosmita Ambarita; Mulyadi Mulyadi (PROJECT (Professional Journal of English Education), 2020)
This article discusses several points on the topic of Indonesian relative clauses and some foreign languages. The method used in this research is descriptive contrastive  analysis. The focus is on finding some results from previous papers on how the languages share similarities and differences as well as how they differ with English. In this case it was found that Indonesian relative clauses are known as being distinctive and different from structured English counterparts. Meanwhile, there is a tendency that relative Indonesian clauses always use passive constructs to relate noun phrases or nouns in complex sentences. Keywords:  Relative Clauses, Foreign Language